2019
DOI: 10.1007/s10840-019-00696-8
|View full text |Cite
|
Sign up to set email alerts
|

The impact of catheter ablation of atrial fibrillation on the left atrial volume and function: study using three-dimensional echocardiography

Abstract: Purpose The exact correlation between the baseline left atrial (LA) volume (LAV) and atrial fibrillation (AF) radiofrequency catheter ablation (RFCA) outcomes and changes to the LA after AF RFCA has not yet been fully understood. We sought to evaluate the serial changes in the LAV and LA function after RFCA using 3D echocardiography. Methods Consecutive patients who received RFCA of paroxysmal (PAF) or persistent AF (PeAF) at our center between January 2013 and March 2016 were included. Real-time 3D apical ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 22 publications
1
11
0
5
Order By: Relevance
“…Based upon the fact that LA function was improved in both groups it might be concluded that most of the effects appeared to result from ablation, not LAAC. Previous studies demonstrated that persistent AF ablation was associated with a dramatic improvement in mechanical cardiac functions, and this evidence further supports our inference (16,17). Moreover, simple CA can achieve better improvement of LA function as compared to the combined therapy before 3 months, and the difference between the two groups in LA reservoir and conduit function as assessed by strain indices began very early, from 1 week to 3 months after surgery.…”
Section: Discussionsupporting
confidence: 89%
“…Based upon the fact that LA function was improved in both groups it might be concluded that most of the effects appeared to result from ablation, not LAAC. Previous studies demonstrated that persistent AF ablation was associated with a dramatic improvement in mechanical cardiac functions, and this evidence further supports our inference (16,17). Moreover, simple CA can achieve better improvement of LA function as compared to the combined therapy before 3 months, and the difference between the two groups in LA reservoir and conduit function as assessed by strain indices began very early, from 1 week to 3 months after surgery.…”
Section: Discussionsupporting
confidence: 89%
“…Данное обстоятельство, вероятно, связано: 1) с применением разного программного обеспечения (Soft) УЗИ-сканнеров, обеспечивающего один из двух возможных подходов, регистрирующим стрейн ЛП, либо от начала комплекса QRS (первый пик позитивный -в фазу резервуара ЛП), либо от начала зубца P на ЭКГ (анализируется первый негативный пик, соответствующий систоле ЛП); 2) значениями S ЛП, получаемыми в сроки наблюдения (follow up) от 3 мес. до 1,5 лет после проведения РЧА [2,9].…”
Section: Relationships Andunclassified
“…После самой процедуры РЧА динамика показателей объёма и S ЛП, как выяснили корейские учёные, проходит неоднозначно в течение 12 мес. наблюдения [2]. В исследование были включены 99 пациентов: средний возраст составлял 58,0±8,2 года, 75 больных (74,7%) мужчины, пароксизмальная ФП -59 пациентов (60%) и персистирующая ФП -40 пациентов (40%).…”
Section: Relationships Andunclassified
See 2 more Smart Citations